Bulbophyllum (Orchidaceae) in the flora of Vietnam III. The revision of B.sect. Lemniscata - Averyanov, Leonid V.; Truong, Ba Vuong; Maisak, Tatiana V. (Phytotaxa, 2019)
Modern taxonomic revision of Bulbophyllum sect. Lemniscata in the flora of Vietnam based on available collections and literature data reports 5 species (Bulbophyllum averyanovii, B. chelicerum, B. comosum B. hirtum, and B. lemniscatoides), one of which (B. chelicerum) is described as a new for science. For all accepted taxa the paper provides valid name and main synonyms with appropriate standard taxonomic references, data on type and other authentic materials, description, data on ecology, phenology, expected conservation status, distribution, notes on biology and taxonomy, list of all studied materials, as well as key for identification of species and their color illustrations. Lectotype for B. lemniscatoides is proposed.